THE RELATIONSHIP BETWEEN ADVERSITY INTELLIGENCE AND SENSATION SEEKING AMONG NATURE LOVERS COLLEGE STUDENTS IN SEMARANG - Ari Wahyuni; Achmad Mujab Masykur (Jurnal EMPATI, 2013)
This study aims to determine the relationship between Adversity Intelligence andSensation Seeking in Nature Lovers Students in Semarang. Study population asmuch as 258 students from 18 University nature lovers organizations in Semarangwith as many as 149 students as a sample. Sampling technique using proportionalrandom sampling. Methods of data collection in this study using AdversityIntelligence Scale and the Sensation Seeking Scale. Analysis of data using simplelinear regression analysis.Simple linear regression analysis showed a positive and significant relationshipbetween Adversity Intelligence and Sensation Seeking on nature lovers student. Itcan be seen from the magnitude of the rxy = 0.277 p = 0.001 (p <0,05). Rxy valuesindicate positive direction of the correlation between the two variables, meaningthat the higher Adversity Intelligence, the higher Sensation Seeking, andconversely the lower Adversity Intelligence, the lower Sensation Seeking.Adversity Intelligence give 7.7% effective contribution value of the SensationSeeking. This result indicates that the level of Sensation Seeking consistency7.7% can be predicted by Adversity Intelligence, while the remaining 92.3% isdetermined by other factors that are not revealed in this study such as age,environment, education and sosioeconomic conditions.